Germline RB1 Mutation in Retinoblastoma Patients: Detection Methods and Implication in Tumor Focality - Rojanaporn D. (2023)
Purpose: The study aimed to generate a stepwise method to reduce the workload of full-scale RB1 sequencing for germline mutation screening in retinoblastoma (RB) patients. The implication of germline mutation in tumor focality was also determined in this study. Methods: A stepwise method was created on the basis of “hotspot” exons analyzed using data on germline RB1 mutation in the RB1–Leiden Open Variation Database and then tested for mutation screening in the blood DNA of 42 patients with RB. The method was compared with the clinical next-generation sequencing (NGS) panel in terms of sequencing outcomes. The germline RB1 mutation was examined in association with multifocality in RB. Results: Germline RB1 mutation was identified in 61% of all bilateral cases in the first step of the 3 stepwise method and in 78% and 89% for the two and three steps combined, respectively. NGS detected a mosaic variant of RB1 that was not detected by the first two steps and increased the sensitivity from 78% to 83%. Analysis of the relation-ship between mutation status and tumor focality indicated that multifocality in RB was dependent on germline RB1 mutation, confirming a higher tendency to have a germline RB1 mutation in patients with multifocal RB. Conclusions: A 3 stepwise method reduces the workload needed for sequencing of the RB1 for bilateral cases. NGS outweighs conventional sequencing in terms of the identi-fication of germline mosaic variants. Multifocal tumors in RB may be used to presume germline mutation. Translational Relevance: The presence of “hotspot” exons of germline RB1 mutation in bilateral cases facilitates a mutation screening. However, when genetic testing is not available, multifocality in RB regardless of tumor laterality is predictive of germline RB1 mutation.